2015
DOI: 10.5562/cca2782
|View full text |Cite
|
Sign up to set email alerts
|

Variable Temperature 57Fe-Mössbauer Spectroscopy Study of Nanoparticle Iron Carbides

Abstract: Near-phase-pure nanoparticle iron carbides (Fe3C and Fe5C2) were synthesised. Debye model calculations were used with hyperfine parameters gathered by 57 Fe Mössbauer spectroscopy within a temperature range of 10 K to 293 K, with analysis providing Debye temperatures of 422 K and 364 K for two Fe sites in Fe5C2 and 355 K for ferromagnetic Fe3C. The intrinsic isomer shifts were calculated as 0.45 mm s −1 and 0.43 mm s −1 for iron sites 1 and 2 respectively in Fe5C2 and 0.42 mm s −1 for Fe3C. Recoil-free fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The parameters of the sextet are close to those reported for Fe 3 C (a catalyst used during CNT production [ 39 , 40 ]). As in previous studies we observe a significant reduction in the magnetic hyperfine field and an increase in the line width in comparison to pure Fe 3 C [ 41 , 42 ]. We interpret the deviation as being caused by extensive local disorder in the Fe 3 C particles of MCNT-Wako.…”
Section: Resultssupporting
confidence: 89%
“…The parameters of the sextet are close to those reported for Fe 3 C (a catalyst used during CNT production [ 39 , 40 ]). As in previous studies we observe a significant reduction in the magnetic hyperfine field and an increase in the line width in comparison to pure Fe 3 C [ 41 , 42 ]. We interpret the deviation as being caused by extensive local disorder in the Fe 3 C particles of MCNT-Wako.…”
Section: Resultssupporting
confidence: 89%
“…7b and S7†), which may lead to different catalytic properties. 69,70 According to a literature survey (Table S8†), the contents of the specific Fe sites in Fe 5 C 2 (the Fe in sites II and III) and O/P are positively correlated, favouring the inhibition of carbon chain growth reactions and promoting olefin production, which further supports our conclusion that the content of the specific Fe sites in Fe 5 C 2 (sites II and III) has a modulating effect on O/P and olefin selectivity. On the basis of our findings, it can be concluded that: (1) doping of metal promoters into iron-based catalysts not only has an effect on the Fe 5 C 2 content, but also changes the content of the different Fe sites within Fe 5 C 2 (sites I, II and III); (2) the content of the specific Fe sites within Fe 5 C 2 (sites II and III) should be responsible for the O/P ratio and olefin selectivity.…”
Section: Resultssupporting
confidence: 82%
“…Indeed, the Mössbauer analyses of the used in the catalytic test materials demonstrated disappearance of the sextets attributable to the substituted magnetite (Table 4, Figures S5 and S6). Instead, a new sextet component with an isomer shift of about 0.2 mm/s and a low hyperfine field, typical of Fe3C carbide, were detected [75,76]. With the increase in the Co/Zn ratio in the samples, an additional low-intensive sextet with parameters attributable to an α-(Fe, Co) alloy appeared.…”
Section: Catalytic Testsmentioning
confidence: 97%